Answer:
3
Explanation:
![f^(-1)(2)=b \text{ implies } f(b)=2](https://img.qammunity.org/2020/formulas/mathematics/middle-school/b37o9j0ghqgzf2r68gmztjw06t2nhh0k73.png)
This we means to to solve the following equation for b:
![f(b)=\log_2(b+1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/9357djm9634mcpqz1uqkgq0dvwny4byjme.png)
since f(b)=2
Write in equivalent exponential form:
![2^2=b+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dtyfpzrzn2xfm5pycxmxxdb2fwj9v01153.png)
![4=b+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/z2w1nvlefbbqhtxmgokj9b1sgqu86lssm6.png)
Subtract 1 on both sides:
![4-1=b](https://img.qammunity.org/2020/formulas/mathematics/middle-school/kw7e6lpo8o649gaqnl6zkqg9fvo5hnei2s.png)
![3=b](https://img.qammunity.org/2020/formulas/mathematics/middle-school/bcds41cawg5i1u1j02l51xybtbap707z2h.png)
This means
![f(3)=2 \text{ so } f^(-1)(2)=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p5oqyld8bew13ivm1ceu358h5k3th1dp2p.png)
You could actually find the inverse function if you want to then replace input for the inverse with 2.
![y=\log_2(x+1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c1her7h6fjyx9w4pjweo3js8gx6lb1llqw.png)
Your logarithm has base 2 and input (x+1) and output y.
The equivalent exponential form is:
![2^(y)=x+1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d6tt57c6eck6ji0qt36w13yo1pxgys89c1.png)
If we solve for x then at the end swap x and y we would have found the inverse function.
Let's do that:
![2^y=x+1</p><p>Subtract 1 on both sides:</p><p>[tex]2^y-1=x](https://img.qammunity.org/2020/formulas/mathematics/middle-school/p4nhptsk9pez3wa2mof2iihf9689xq6v0n.png)
Swap x and y:
![2^x-1=y](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cfsw6jiz5a0ry4afhja5o5baouuvrbnlft.png)
The inverse function of our given function is:
![f^(-1)(x)=2^x-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/516hphllvf3eefmbpnbb069hoz9lppyzl7.png)
Now we need to replace x with 2:
![f^(-1)(2)=2^2-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2s7r3yry1tqe4ohfss662ztatqoaxm9ov3.png)
![f^(-1)(2)=4-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ag5fi7cykp3cl94g5on5jrudd98ze753fc.png)
![f^(-1)(2)=3](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t2hrq4rblga4wh0a3kt8uw62ioqn3ux8ko.png)